2014
DOI: 10.1371/journal.pone.0107362
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of GOLPH3 Associated with the Progression of Gastric Cancer: A Preliminary Study

Abstract: Study DesignTo investigate the specific mechanisms by which Golgi phosphoprotein 3 (GOLPH3) affects the progression of gastric cancer and to explore its clinical significance.MethodsImmunohistochemical analysis was used to evaluate the correlations between GOLPH3, phosphorylated mTOR (p-mTOR), phosphorylated Akt (p-Akt), phosphorylated p70S6 (p-p70S6), phosphorylated 4E-BP1 (p-4E-BP1) and the clinicopathological features of gastric cancer. The mRNA expression levels of GOLPH3, mTOR, Akt, p70S6 and 4E-BP1 in ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 30 publications
2
22
0
Order By: Relevance
“…Similarly, Murayama et al reported that p-mTOR expression was positively correlated with GC tumor invasion and tumor stage (31). In addition, a preliminary study revealed that GOLPH3 was positively correlated with Akt/mTOR activation in GC (18). In line with these studies, we showed in the present study that the phosphorylation of AKT, mTOR and mTOR downstream substrate protein S6K were impaired by miR-134 overexpression, while overexpression of GOLPH3 restored this effect caused by miR-134, suggesting that miR-134 regulated this AKT/mTOR/S6K signaling pathway via a GOLPH3-dependent mechanism.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Similarly, Murayama et al reported that p-mTOR expression was positively correlated with GC tumor invasion and tumor stage (31). In addition, a preliminary study revealed that GOLPH3 was positively correlated with Akt/mTOR activation in GC (18). In line with these studies, we showed in the present study that the phosphorylation of AKT, mTOR and mTOR downstream substrate protein S6K were impaired by miR-134 overexpression, while overexpression of GOLPH3 restored this effect caused by miR-134, suggesting that miR-134 regulated this AKT/mTOR/S6K signaling pathway via a GOLPH3-dependent mechanism.…”
Section: Discussionmentioning
confidence: 87%
“…4A). Moreover, a recent study showed that the mRNA level of GOLPH3 is upregulated in GC tissue and is positively associated with cell proliferation (18). Given this evidence and the observed function in miR-134-overexpressing cell lines and mice, we speculated that GOLPH3 was a target of miR-134.…”
Section: Mir-134 Is Downregulated In Gcmentioning
confidence: 84%
“…An increasing number of papers has shown that GOLPH3 drives cancer in several other solid tumors such as Neuroblastoma (NB) [42], Non-Small Cell Lung Cancer (NSLC) [89], epithelial ovarian carcinoma [90], prostate cancer [91,92], gastric cancer [93], and hepatocellular carcinoma [94,95] ( Figure 2). Recent reports indicate that GOLPH3 overexpression can be used as a positive biomarker for tumor progression and poor survival in these cancer types [89][90][91][92][93][94][95][96][97][98]. Experimental data in cancer cell lines or in nude mice revealed the role of GOLPH3 in cell proliferation, metastasis formation and angiogenesis ( Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence of transformation by overexpression of GOLPH3 has been reported in MDA-MB-231 and MCF7 breast cancer cell lines (911), and U251 and U87 glioblastoma cell lines (12, 13). Frequent overexpression of GOLPH3 and correlation with poor prognosis have been reported in multiple tumor types including 58–72% of non-small cell lung cancers (14, 15), 52% of breast cancers (11), 70% of prostate cancers (16), 73% of pancreatic ductal adenocarcinomas (17), 65% of hepatocellular carcinomas (18, 19), 55–58% of gastric cancers (20, 21), 53% of renal cell carcinomas (22), 41–53% of glioblastomas (12, 23, 24), 49% of esophageal squamous carcinomas (25), and 45% of ovarian carcinomas (26, 27). Overexpression of GOLPH3 occurs frequently in rhabdomyosarcoma, and knockdown of GOLPH3 in rhabdomyosarcoma cell lines impairs cell proliferation (28).…”
Section: Golph3 Is An Oncogenementioning
confidence: 99%